Articulation in Education - Buffer, Loretta C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
One of a series of papers on critical issues in vocational-technical education, this paper discusses problems and possible solutions to the need for special consideration of individual needs as students migrate within and between educational programs. Articulation is required so that students may move from program to program, or from institution to institution, with a minimum of wasted time and duplicated effort. Problem areas in planning for articulation that are identified and discussed are students, curriculum and instruction, student personnel services, facilities and resources, mistrust among faculties, and institutional autonomy . What some states are doing in regard to articulation is described briefly, and a discussion of the future of articulation is included. (HD)
ERIC Note: Parts of the 6-page bibliography may not reproduce well because of light, broken type. Paper presented at the Southern Region Vocational Education Leadership Development Conference (Atlanta, Georgia, April 4-7, 1976). For related papers see CE 008 557-570.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Articulation (Education); Curriculum; Educational Problems; Educational Trends; Institutional Cooperation; Program Development; Vocational Education; Speeches/Meeting Papers